(untitled) (Journal of University of Babylon for Engineering Sciences, 2022)
The purpose of this study is to examine using statistics in hydrology for analyzing outflow discharge in Hadith Dam. Total annual outflow data of thirty years for period from 1991to 2020 were used. Mathematical equation for the probability distribution functions were established for the data. Three tests were used, namely (Anderson-Darling, Ryan- Joiner Similar to Shapiro-Wilk and Kolmogorov- Smirnov) to check the normality of the data; the predicted values were subjected to goodness of fit tests such as kolmogorov-smirnov to determine the distribution which is suitable for the data. Depending on the kolomogrov-smirnov (k-s) index, the distributions were suitable for the data, therefore, all the fitted distributions were typical for the data that were used in this paper depending on (k-s) index.